Adsorption Kinetics Study of Cr (III) Metals Using Activated Natural Zeolite - Retno Khimantoro; Sunarno Sunarno; Silvia Reni Yenti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Several methods have been developed to reduce and minimize the presence of copper heavy metals that pollute waters, such as by adsorption method, is one of the natural  zeolite material is widely used as an adsorbent. Natural zeolites have potential as adsorption heavy metals in waste water treatment due to adsorption capacity and high selectivity, long-lived, and the numbers are abundant in Indonesia. Research studies of metal adsorption kinetics of Cr  (III) with activated natural zeolite aims to determine a suitable kinetic model for metal adsorption kinetics of Cr  (III) with activated zeolite  adsorption evaluate the metal Cr  (III) and the effect of temperature on the adsorption rate constant. This study begins with the activation of natural zeolite in physics and chemistry and to be continued to Cr  (III) metal adsorption by activated natural zeolite with a variety of contact time and temperature. Results spectrophotometer adsorption measured using atomic absorption (AAS). From the research that has been done shows that a suitable model for the kinetics of adsorption of metal Cr  (III) with zeolite activated following the model of first  order with a value of k= 0,011  min-1 for a temperature variation of 300C, 400C, 500C. From the results obtained conclude that the higher the temperature will be faster the rate of adsorption and the amount of activation energy values obtained in the amount of 296,73 J/mole, which means that  the adsorption process takes place in physics. Keyword: adsorption kinetics, Cr (III) metal, natural zeolites, adsorption .